MOOCs: The Factors Impacting Learners’ Continuance Intention, the Intention to Complete or Cancel a Course - Adomaviciute, Karina; Dikcius, Vytautas; Zimaitis, Ignas (Organizations and Markets in Emerging Economies, 2023)
The growing popularity of massive open online courses (MOOCs), especially during the COVID-19 pandemic, has attracted significant attention from researchers and businesses. Though many studies have investigated what motivates learners’ continuance intention, it is no less important to reveal the factors that lead to course completion or cancellation. The aim of this study is to reveal the factors impacting three different e-learning behaviour intentions– continuance intention, the intention to complete, and the intention to cancel MOOCs – by applying the theory of planned behaviour (TPB) and the technology acceptance model (TAM). Based on a survey of 299 respondents, it was revealed that the TAM only explains continuance intention but cannot be fully employed to predict two other e-learning behavior intentions. Also, participants’ support and self-efficacy, being a part of the TPB model, had an influence on the intention to complete the course, while they did not affect continuance intention. Only participants’ support had a moderate positive impact on the intention to cancel it. Moreover, it was revealed that continuance intention positively impacted the intention to complete and negatively impacted the intention to cancel the course. This expands the body of knowledge about learners’ motivations for three different e-learning behaviour intentions and has managerial implications for their development in emerging economies.
Keywords: massive open online courses; perceived usefulness; perceived enjoyment; perceived ease of use; participants‘ support; self-efficacy; e-learning behaviour intentions